THERAPY (ACT) TECHNIQUES TO REDUCE INSECURITY IN TATTOOED ADOLESCENTS IN SOCIALIZING IN THE COMMUNITY : CASE STUDY OF CLIENT B IN LUBUK TANJUNG VILLAGE - Windiani, Putri; Razzaq, Abdur; Fitri, Hartika Utami (Jurnal Konseling Pendidikan Islam, 2024)
This research aims to find out the factors that influence self-confidence and find out how to apply Acceptance and Commitment Therapy techniques to reduce the lack of self-confidence. The approach used in this research is using a qualitative approach using field research. The data collection techniques use observation, interviews, and documentation methods. Meanwhile, the data analysis techniques used are done by pattern matching, data explanation, and time series analysis. The results of this research indicate that the factors that influence Client B's self-confidence are two internal factors and external factors. After using the Acceptance and Commitment Therapy technique, there appeared to be a change where client "B" had experienced a change in lack of self-confidence.